Developing Social Accounting Competencies through IoT-Based Goat Farming Learning Systems - Suhardjo Suhardjo; Nicholas Renaldo; Achmad Tavip Junaedi; Kristy Veronica; Harry Patuan Panjaitan; Onny Setyawan; Wilda Susanti; Rahma Widi; Umar Faruq; Jahrizal Jahrizal (Reflection: Education and Pedagogical Insights, 2026)
The digital transformation of agriculture has created new opportunities and challenges for accounting education, particularly in developing social accounting competencies related to sustainability and social responsibility. This study aims to examine the effect of an IoT-based goat farming learning system on the development of social accounting competencies in vocational and applied accounting education. Using a quantitative explanatory research design, this study integrates a technology-enhanced learning approach supported by real-time data generated from IoT-enabled goat farming systems. Data were collected from students participating in IoT-based learning activities and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that the IoT-based goat farming learning system has a positive and significant effect on social accounting competencies, including the ability to identify, measure, interpret, and report social and environmental impacts. The findings demonstrate that real-time livestock data provide an effective experiential learning environment that bridges the gap between abstract social accounting concepts and practical applications. This study contributes to accounting education literature by repositioning IoT-based livestock systems as pedagogical platforms rather than purely operational tools. The study also offers practical implications for educators, curriculum designers, and policymakers seeking to strengthen sustainability-oriented accounting education in digitally transformed agribusiness contexts.